Qualitative evaluation of a community health representative program on patient experiences in Navajo Nation - Amber Lalla; Shine Salt; Elizabeth Schrier; Christian Brown; Cameron Curley; Olivia Muskett; Mae-Gilene Begay; Lenora Shirley; Clarina Clark; Judy Singer; Sonya Shin; Adrianne Katrina Nelson (BMC, 2020)
Abstract Background Community Health Representatives (CHRs) overcome health disparities in Native communities by delivering home care, health education, and community health promotion. The Navajo CHR Program partners with the non-profit Community Outreach and Patient Empowerment (COPE), to provide home-based outreach to Navajo clients living with diabetes. COPE has created an intervention (COPE intervention) focusing on multiple levels of improved care including trainings for CHRs on Motivational Interviewing and providing CHRs with culturally-appropriate education materials. The objective of this research is to understand the participant perspective of the CHR-COPE collaborative outreach through exploring patient-reported outcomes (PROs) of clients who consent to receiving the COPE intervention (COPE clients) using a qualitative methods evaluation. Methods Seven COPE clients were selected to participate in semi-structured interviews one year after finishing COPE to explore their perspective and experiences. Qualitative interviews were recorded, transcribed, and coded to identify themes. Results Clients revealed that health education delivered by CHRs facilitated lifestyle changes by helping them understand key health indicators and setting achievable goals through the use of accessible material and encouragement. Clients felt comfortable with CHRs who respected traditional practices and made regular visits. Clients also appreciated when CHRs educated their family members, who in turn were better able to support the client in their health management. Finally, CHRs who implemented the COPE intervention helped patients who were unable to regularly see a primary care doctor for critical care and support in their disease management. Conclusion The COPE-CHR collaboration facilitated trusting client-CHR relationships and allowed clients to better understand their diagnoses. Further investment in materials that respect traditional practices and aim to educate clients' families may foster these relationships and improve health outcomes. Trial registration clinicaltrials.gov: NCT03326206. Registered 9/26/2017 (retrospectively registered).